1995
DOI: 10.1007/bf00032249
|View full text |Cite
|
Sign up to set email alerts
|

Potential and pitfalls of trying to extend symbiotic interactions of nitrogen-fixing organisms to presently non-nodulated plants, such as rice

Abstract: IntroductionPlant-microbe signalling, nodulation, and symbiotic nitrogen fixationThe oxygen paradox and other potential problems related to microbial nitrogen fixation in novel physiological environments Nodulation of cereals: What has been tried, what has been published, and is nodulation really necessary to achieve useful levels of nitrogen fixation Induction of hypertrophies on rice roots and their colonization by microbes Materials and methods Induction and microscopic examination of "nodule-like" structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This topic is discussed in detail by de Bruijn (1995) and it is clear that enormous physiological and biochemical obstacles need to be surmounted before the goal of N2-fixing cereal crops will be realised. The potential benefits of N2-fixing rice varieties, for example, are enormous.…”
Section: Engineering Of Cereals For N2-fixationmentioning
confidence: 99%
“…This topic is discussed in detail by de Bruijn (1995) and it is clear that enormous physiological and biochemical obstacles need to be surmounted before the goal of N2-fixing cereal crops will be realised. The potential benefits of N2-fixing rice varieties, for example, are enormous.…”
Section: Engineering Of Cereals For N2-fixationmentioning
confidence: 99%
“…The idea that certain rhizobia may intimately colonize rice roots in nature originates from the concept that roots of healthy plants, grown in natural soil, eventually develop a continuum of root-associated microbial colonizations that extend from the rhizosphere to the rhizoplane, and even deeper into the epidermis, cortex, endodermis, and vascular system (Old and Nicolson 1975;Balandreau and Knowles 1978;Old and Nicolson 1978;Klein et al 1990;de Bruijn et al 1995;Stoltzfus et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…This may aid the study of nodule morphogenesis in newly found symbiotic legume species. Moreover, investigation of the intercellular spreading mode, in being simple and sharing common features with infection processes in some nitrogen‐fixing non‐legumes [17], may yield insights that could provide a framework on how to extend nodulation to agronomically important plant species [18, 19]. However, it must be emphasized that not all non‐legumes are invaded via crack entry, it is not the rule [20].…”
Section: Introductionmentioning
confidence: 99%